(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Nanocrystals are small particles whose size typically range from 1 to 100 nm. Nanocrystal-based nanosuspension is a drug delivery technique that involves incorporating drug nanocrystals into a nanosuspension matrix. The nanocrystal-based nanosuspension approach can be particularly useful for drugs with poor solubility or low bioavailability. The current study aimed to develop and characterize a nanocrystals-based nanosuspension of Candesartan cilexetil (CC). In the preparation, CC loaded nanosuspension was prepared employing Eudragit RLPO and PVA as a stabilizer by using solvent precipitation method. The drug content (%), DR (%) and zeta potential are performed for all formulations. The optimized formulation (CCSD2) had a particle size of 221 nm, a zeta potential of 30.4 mv, and a drug release rate of 95.58%, and it was used for further testing. The optimized formulation had a polydispersity index (PDI) of 0.218. SEM revealed drug nanocrystals agglomeration, which could have been caused by the water removal process. DSC showed a minor change in crystallinity, which could be attributed to the presence of lactose. The stability trial lasted 6 months. The solvent precipitation method is an efficient way to create CC nanocrystal with lower particle size. DSC thermogram confirmed no interaction between drug and excipients. The DR release study of CC nanosizing method. CC are efficiently and successfully confined inside the polymer. CC and other class II medicines may therefore find a promising carrier in the nanocrystal method.